On the viscosity maximum during uniaxial extension: Material property or measuring artifact? - Stary, Zdenek; Burghelea, Teodor; Münstedt, Helmut (AIP Conference Proceedings, 2013)
An experimental investigation of the viscosity maximum observed during uniaxial extension of a low density polyethylene is presented. For this purpose, traditional integral viscosity measurements on a Münstedt-type extensional rheometer are combined with local measurements based on the in-situ visualization of the sample under extension. For elongational experiments at intermediate constant strain rates local maximum of the extensional viscosity is systematically observed. Images of samples within this regime show that secondary necks develop along the sample at the moment when the maximum of the integral viscosity is observed. The emergence of a maximum of the integral elongational viscosity is, thus, related to the distinct non-uniformity of deformation states and most probably not to the rheological properties of the material. Moreover, the position of the viscosity maximum was found to be dependent on the initial geometry of the specimen. This indicates again that the appearance of the transient viscosity maximum is not a material property but an artifact caused by a geometrical non-uniformity of highly stretched specimens. © 2013 AIP Publishing LLC.
Created from Fastlane, Scopus look-up
Keywords: Elongational flow; Polymer melts; Rheology